Bioactivity-guided fractionation of Helicteres angustifolia L. extract and its molecular evidence for tumor suppression - Li, Kejuan; Sun, Shuang; Xiao, Long; Zhang, Zhenya (Frontiers in Cell and Developmental Biology, 2023)
Helicteres angustifolia L. (Helicteres angustifolia) has been commonly used in folk medicine to treat cancer; however, its mechanisms of action remain obscure. In our earlier work, we reported that aqueous extract of H. angustifolia root (AQHAR) possesses attractive anticancer properties. In the present study, we isolated five ethanol fractions from AQHAR and investigated their therapeutic efficacy in human non-small cell lung cancer (NSCLC) cells. The results showed that among the five fractions, the 40% ethanol fraction (EF40) containing multiple bioactive compounds exhibited the best selective killing effect on NSCLC cells with no obvious toxicity to normal human fibroblasts. Mechanistically, EF40 reduced the expression of nuclear factor-E2-related factor 2 (Nrf2), which is constitutively expressed at high levels in many types of cancers. As a result, Nrf2-dependent cellular defense responses are suppressed, leading to the intracellular accumulation of reactive oxygen species (ROS). Extensive biochemical analyses revealed that EF40 caused cell cycle arrest and apoptosis through activation of the ROS-mediated DNA damage response. Furthermore, treatment with EF40 compromised NSCLC cell migration, as evidenced by the downregulation of matrix metalloproteinases (MMPs) and heterogeneous nuclear ribonucleoprotein K (hnRNP-K). In vivo studies using A549 xenografts in nude mice also revealed significant suppression of tumor growth and lung metastasis in the treated group. We propose that EF40 may serve as a potential natural anti-NSCLC drug that warrants further mechanistic and clinical attention.